2001
DOI: 10.2169/internalmedicine.40.972
|View full text |Cite
|
Sign up to set email alerts
|

Rapidly Progressive Tabes Dorsalis Associated with Selective IgA Deficiency.

Abstract: Tabes dorsalis is uncommonand progresses slowly from infection to clinical manifestation. Wereport a rare case of rapidly progressive tabes dorsalis associated with selective IgA deficiency (slgAD). A 28-year-old man was hospitalized with lightning back pain, nausea, and bladder bowel dysfunction. Serum and cerebrospinal fluid (CSF) revealed high titers of Treponema pallidum antibody, and the serum IgA level was less than 5 mg/dl. Thl-dominant cytokine expression was observed, as is usually seen in neurosyphil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
3
0
1
Order By: Relevance
“…An anecdotal exception could be represented by a literature report of rapidly progressive tabes dorsalis that occurred in a 28-year-old patient with an IgA immunodeficiency. 7 A low clinical suspicion due to the young age, negative syphilis testing obtained a decade before, negligible recent sexual history, absence of CSF leukocytes, and the need to exclude all other possible aetiologies hampered a prompt recognition of tertiary neurosyphilis in our case. The possible cross-reaction of syphilis and borrelia serology 8,9 also contributed to delay both recognition and selective treatment of neurosyphilis.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…An anecdotal exception could be represented by a literature report of rapidly progressive tabes dorsalis that occurred in a 28-year-old patient with an IgA immunodeficiency. 7 A low clinical suspicion due to the young age, negative syphilis testing obtained a decade before, negligible recent sexual history, absence of CSF leukocytes, and the need to exclude all other possible aetiologies hampered a prompt recognition of tertiary neurosyphilis in our case. The possible cross-reaction of syphilis and borrelia serology 8,9 also contributed to delay both recognition and selective treatment of neurosyphilis.…”
Section: Discussionmentioning
confidence: 82%
“…The ceftriaxone-tetracycline association, started when neuroborreliosis was still suspected, 9 is not the first-choice neurosyphilis therapy, although both cefriaxone and tetracyclines may act favourably in patients with primary-secondary syphilis, 3,5 and in tertiary CNS localizations too. [5][6][7]11,12 This is due to the favourable antimicrobial activity associated with elevated CNS penetration of ceftriaxone. Presently, the main penicillin alternative remains doxycycline, and the place of ceftriaxone and azithromycin, although promising, cannot be established due to the lack of randomized trials.…”
Section: Discussionmentioning
confidence: 99%
“…In 2001, Nishimura et al . reported a 28‐year‐old man with rapidly progressive tabes dorsalis associated with selective IgA deficiency 12 . They suggested that ‘the atypical rapid course of this patient was possibly due to this selective IgA deficiency’.…”
Section: Discussionmentioning
confidence: 98%
“…tabes -разложение, тление, гниение), в допенициллиновую эпоху считалась патогномоничной и самой распространенной формой НС. После внедрения в практику пенициллина СС регистрировалась казуистически редко, однако в последние годы сообщения о случаях данной патологии все чаще появляются как в отечественной [14][15][16][17][18][19], так и в зарубежной [20][21][22] литературе. Имеются также единичные сообщения о СС у инфицированных ВИЧ [23,24].…”
Section: Discussionunclassified